Current Ratio, Return on Assets, and Dividend Payout Ratio’s Roles on Stock Prices - Zuchruf Firdaus; Sujianto Sujianto (GOVERNORS, 2025)
The objective of this study is to determine and analyze the effect of the Current Ratio (CR), Return on Assets (ROA), and Dividend Payout Ratio (DPR) on stock prices of financial companies in the Trade and Investment Services sector listed on the Indonesia Stock Exchange during the period 2017–2021. This study employs a quantitative research approach. The research sample consists of financial companies in the Trade and Investment Services sector listed on the Indonesia Stock Exchange from 2017 to 2021. Based on the sampling criteria, six companies were selected, with annual data over a five-year period.  Data Analysis Using Classical Assumption Test and Multiple Linear Regression The results of the study indicate that, partially, there is a proven effect (linear relationship) between the Current Ratio and stock prices. There is also a proven effect (linear relationship) between Return on Assets and stock prices. Furthermore, the Dividend Payout Ratio is proven to have an effect (linear relationship) on stock prices. Subsequently, fundamental factors consisting of the Current Ratio, Return on Assets, and Dividend Payout Ratio simultaneously or jointly are proven to have a positive effect on stock prices of companies in the Trade and Investment Services sector listed on the Indonesia Stock Exchange.